Adecuación de un Canal Digital para la Emisora de la Universidad Distrital Francisco José de Caldas - Castañeda Fandiño, José Ignacio (Ingeniería, 2004)
The Data Transmition through audio's signal of a FM's broadcasting station is possible thanks to wide band (WB) available. This paper describes one solution to improve a last project, which was implemented to transmit data using the WB dedicated to this porpouse. It explain how a WB more narrow is used and also is possible a greater transmition rate, showing comparatively the advantages that accompany to the new system.